Republic of Madagascar : Second Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Republic of Madagascar. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
Madagascar has not yet recovered from the pandemic and is struggling with the aftermath of a severe cyclone season and the fallout of Russia's war in Ukraine. After a sharp contraction of GDP in 2020 (-7.1 percent) and a modest recovery in 2021 (4.3 percent), growth is projected to stall in 2022. Lower demand from trading partners, higher fuel and food prices, and recent weather events are weighing on economic activity and leading to widening fiscal and external deficits in the short term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Madagascar, Republic of